First record of Geoglossum fallax (Geoglossaceae, Ascomycota) in the southernmost region of the state of Bahia, northeastern Brazil (Bioscience Journal, 2020)
Informally known as black earth tongue, Geoglossum fallax has a large terrestrial dark brown or black ascoma. The species belongs to the Geoglossomycetes class of fungi, which includes the genera Geoglossum, Sarcoleotia, Thuemenidium and Trichoglossum. This study describes the first record of G. fallax in Bahia, northeastern Brazil, and presents the species’ main identification features. The specimens were found growing on a lawn, in Campus X, Bahia State University (UNEB), municipality of Teixeira de Freitas, southernmost region of Bahia state. After gross inspection and microscopy, all specimens were identified based on the specialized literature. Slides and exsiccata of specimens were deposited in the Fungi Collection, Fungal Biology Laboratory, Campus X, UNEB. This is the first record of G. fallax in northeastern Brazil.